"Some Things Just Won't Go Back": Teen Girls' Online Dating Relationships during COVID-19. Issue 3 (1st December 2020) - Goldstein, Alanna; Flicker, Sarah
Abstract: We conducted three online focus groups [n = 25] with teen girls in Canada in May and June 2020 to explore their dating and relationship experiences during the early stages of the COVID-19 pandemic. Given the strict public health measures limiting physical contact, participants reported connecting primarily online with possible dating partners and others. While facilitating platforms, like Snapchat, were already part of these teen girls' dating and relationships repertoire, many participants reflected on the limitations and drawbacks of being able to connect only virtually. Results suggest the need to better attend to the impacts that COVID-19 restrictions are having on teen girls' dating relationships, as well as to the larger impacts that the deterioration of these relationships might be having on their mental and emotional health.